Total Synthesis of C-8 Hydroxyl Substituted Lomefloxacin as the Photolysis Impurity - Chen, Si; Wang, Ying; Yuan, Xiao; Wang, Laiyou (Letters in Organic Chemistry, 2022)
Photochemical decomposition of lomefloxacin (Lom) is supposed to result in the generation of C-8 substituted impurity and accompanied fluoride. The existence and amount of C-8 hydroxyl substituted Lom could be proposed as the marker to the stability and process consistency. The specific C-8 hydroxyl substituent impurity (1-ethyl-6-fluoro-8-hydroxy-7-(3- methylpiperazin-1-yl)-4-oxo-1,4-dihydroquinoline-3-carboxylic acid) was designed and synthesized to be available.2,4,5-trifluoro-3-methoxybenzoic acid as the initial reactant was subjected to a series of seven-step reactions, such as acylation, condensation with trans N,Ndimethylamino ethyl acrylate, N-ethylation, cyclization, hydrolysis, condensation with piperazine and acidification. The resultant substance was then purified using HPLC and C18 solidphase extraction. The structure of C-8 hydroxyl substituted Lom was identified with 1H-NMR, 13C-NMR and HRMS spectroscopes, as well as the purity was determined by HPLC. C-8 hydroxyl substituted Lom was successfully synthesized and purified with purity more than 96%. This photolysis impurity offers an alternative for not only further generic Lom active pharmaceutical ingredient development involved in quality control and consistency evaluation, but also research for the mechanism underlying Lom-induced photosensitivity.
Keywords: impurity